Erv14 cargo receptor participates in yeast salt tolerance via its interaction with the plasma-membrane Nha1 cation/proton antiporter - Rosas-Santiago, Paul; Zimmermannova, Olga; Vera-Estrella, Rosario; Sychrová, Hana; Pantoja, Omar (Biochimica et biophysica acta, 2016)
The yeast Nha1p Na(+), K(+)/H(+) antiporter has a house-keeping role in pH and cation homeostasis. It is also needed to alleviate excess Na(+) or K(+) from the cytoplasm under high external concentrations of these cations. Erv14p, a putative cargo receptor for transmembrane proteins is required for trafficking of Nha1p from the endoplasmic reticulum to the plasma membrane. Sensitivity to high Na(+) concentrations of the erv14 mutant associated to the intracellular mislocalization of Nha1p-GFP, together with a lower Na(+) efflux, indicate the involvement of this mutual association to accomplish the survival of the yeast cell upon sodium stress. This observation is supported by the protein-protein interaction between Erv14p and Nha1p detected by the mating-based Split Ubiquitin System and co-immunoprecipitation assays. Our results indicate that even though Erv14p interacts with Nha1p through the TMD, the C-terminal is important not only for the efficient delivery of Nha1p to the plasma membrane but also for its dimerization to accomplish its role in yeast salt tolerance.
Keywords: Protein Binding; Saccharomyces cerevisiae Proteins; regulace genové exprese u hub; Potassium; Recombinant Fusion Proteins; Cations, Monovalent; multimerizace proteinu; interakční proteinové domény a motivy; draslík; Mislocalization; Sodium Chloride; Saccharomyces cerevisiae; Salt Tolerance; membránové proteiny; Membrane Proteins; proteiny přenášející kationty; Erv14p; Cation Transport Proteins; sekundární struktura proteinů; rekombinantní fúzní proteiny; kationty jednomocné; Protein Structure, Secondary; chlorid sodný; protony; Protein Interaction Domains and Motifs; Sodium-Hydrogen Exchangers; vazba proteinů; tolerance k soli; biologický transport; Salt-tolerance; Protons; Gene Expression Regulation, Fungal; Yeast; Saccharomyces cerevisiae - proteiny; Protein–protein interaction; Na(+)-H(+) antiport; Nha1p; Biological Transport; Protein Multimerization